2022
DOI: 10.1002/jmri.28547
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric MR Imaging Radiomics Signatures for Assessing the Recurrence Risk of ER+/HER2− Breast Cancer Quantified With 21‐Gene Recurrence Score

Abstract: BackgroundWhile the Oncotype DX 21‐gene recurrence score (RS) has been recommended for guiding ER+/HER2− breast cancer treatment decisions, it is limited by cost and availability.PurposeTo develop a multiparametric MRI‐based radiomics model for assessing ER+/HER2− breast cancer patients' 21‐gene RS.Study TypeRetrospective.SubjectsA total of 151 patients with pathologically confirmed ER+/HER2− breast cancers, who underwent preoperative breast MR examinations and 21‐gene expression assays, divided into training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…Eun et al (2021) demonstrated the superior diagnostic performance of RF model-based texture analysis over conventional MRI and clinicopathological features in predicting breast carcinomatosis recurrence after NAC(AUC: 0.94 vs. 0.83, P<0.05). Chen et al (2022) dictors, which also successfully predicted DFS in patients with invasive breast cancer.…”
Section: Prediction Of Recurrence and Survival Outcomesmentioning
confidence: 89%
“…Eun et al (2021) demonstrated the superior diagnostic performance of RF model-based texture analysis over conventional MRI and clinicopathological features in predicting breast carcinomatosis recurrence after NAC(AUC: 0.94 vs. 0.83, P<0.05). Chen et al (2022) dictors, which also successfully predicted DFS in patients with invasive breast cancer.…”
Section: Prediction Of Recurrence and Survival Outcomesmentioning
confidence: 89%
“…Based on informal consensus, the panel recommended that oncologists offer chemoendocrine therapy to patients with recurrence scores of 26 to 30 (9). Only one study adopting this cutoff was recently published in literature for assessing ER + / HER2 − breast cancer patients' 21-gene RS using a multiparametric MRI-based radiomics model [49]. They obtained an AUC of 0.82 from DCE of the tumor that improved to 0.92 when adding DWI and T2-weighted images.…”
Section: Discussionmentioning
confidence: 99%
“…In detail, they divided high risk and low-intermedium risk based on a RS cut-off of 25 [9]. In this regard, only one study was recently published on the potential correlation between radiomics and RS adopting this cut-off, but it did not assess the role of peritumoral tissues [49].…”
Section: Introductionmentioning
confidence: 99%
“…However, the predictive performance has varied widely across studies, with the accuracy ranging from 52.5–86.8%. The predictive accuracy has been further improved via the use of clinicopathologic and magnetic resonance imaging (MRI) parameters, with the resulting area under the receiver operating characteristic curve (AUC) for predicting the probability of RS ≥26 ranging from 0.75 to 0.90 ( 9 - 11 ). Ultrasound (US), given its high soft-tissue contrast and sensitivity, is one of the most common modalities used in the diagnosis of breast cancer ( 12 ).…”
Section: Introductionmentioning
confidence: 99%